16-channel dual-tuning wavelength division multiplexer/demultiplexer*Project supported by the National Key Research and Development Program of China (Grant No. 2016YFB0402504) and the National Nature Science Foundation of China (Grant No. 61435013). (December 2018) - Yuan 袁, Pei 配; Wang 王, Yue 玥; Wu 吴, Yuan-Da 远大; An 安, Jun-Ming 俊明; Hu 胡, Xiong-Wei 雄伟
Abstract : A 16-channel dual tuning wavelength division multiplexer/demultiplexer based on silicon on insulator platform is demonstrated, which is both peak wavelength tunable and output optical power tunable. The wavelength division multiplexer/demultiplexer consists of an arrayed waveguide grating for wavelength division multiplexing/demultiplexing, a heater for peak wavelength tuning and a variable optical attenuator based on p–i–n carrier-injection structure for optical power tuning. The experimental results show that the insertion loss on chip of the device is 3.7dB–5.7 dB and the crosstalk is 7.5 dB–9 dB. For the tunability of the peak wavelength, 1.058-nm wavelength tunability is achieved with 271.2-mW power consumption, and the average modulation efficiency is 3.9244 nm/W; for the tunability of the optical power, the optical power equalization is achieved in all 16 channels, 20-dB attenuation is achieved with 144.07-mW power consumption, and the raise/fall time of VOA is 35 ns/42 ns.